Trailblazing 1D gadolinium-doped yttrium aluminium garnet (YAG: Gd3+) nanofibers for UV-optimized applications - Khushbu A. Rathi; Tejaswini A. Rathi; Subhash B. Kondawar; Pankaj Koinkar; Sanjay R. Dhakate (Results in Optics)
This research presents a novel approach to fabricating Yttrium Aluminum Garnet (YAG) nanofibers doped with Gadolinium (Gd3+) ions using the electrospinning technique. Rare earth-doped electrospun nanofibers, known for their exceptional performance, attract significant interest for applications in flexible display devices. While Gd3+-doped YAG materials have been studied, this is the first instance of their synthesis in nanofiber form, enhancing their optical and emission properties, particularly in the ultraviolet-B i.e. UV-B (280–315 nm) range. The study aims to develop and characterize these nanofibers with varying Gd3+ concentrations (x = 0.5, 1, 1.5, 2 mol%), employing techniques like X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-Ray Photoelectron Spectroscopy (XPS), and photoluminescence to analyze structural integrity, surface morphology, and luminescence. XRD confirmed the pure YAG phase after calcination at 950 °C for 2 hrs, and the nanofibers showed a strong emission peak at 313 nm under 274 nm excitation corresponding to the 6P7/2 → 8S7/2 transition, with optimal photoluminescence at 1 mol% Gd3+ doping. These results highlight the potential of Gd3+-doped YAG nanofibers for advanced applications in flexible electronics and UV-based display devices.